STUDI PERBANDINGAN ALASAN PENGHAPUS PIDANA MENURUT KITAB UNDANG-UNDANG HUKUM PIDANA (KUHP) DAN HUKUM PIDANA ISLAM DALAM RANGKA PEMBAHARUAN HUKUM PIDANA NASIONAL - Muhammad Maulana Firdaus; Ira Alia Maerani (Unissula, 2020)
Criminal law is suffering that is deliberately inflicted upon a person who commits an act that meets certain conditions. The purpose of this research is to know the similarities and differences in criminal law enforcement between Dutch inheritance law and Islamic law and to know its contribution to the State of Indonesia.Theaim of this research is to find out the similarities and differences as well as knowing its contribution to the Criminal Code.The method of approach in this research is normative jurisdiction that is research conducted by focusing on the applicable regulations as well as literature or books relating to legal relations, especially regarding the reasons for criminal abolition according to the Criminal Law Act and Islamic criminal law. Based on the results of the study, it can be concluded that the similarities and differences in the reasons for criminal eradication according to the Criminal Codeand Islamic criminal law, the similarity of reasons for the eradication of the two laws are among others: self-defense, forced power, carrying out orders / carrying out duties , unable to take responsibility. Whereas the difference is that Defendants are forced to exceed the limits, carry out the provisions of the law, get drunk, the defendant's death, past time. As well as the contribution of the reasons for the Criminal Eradication in Islamic Criminal Law in the Contribution of the Criminal Codethat will come. The contribution of Islamic law that the author wants to convey in contributing to the renewal that is to come, should be when there is an apology to the victim then abolish the criminal and stop the criminal process.